(untitled) (Comunicação & Inovação, 2024)
Conflicts between creators and companies are challenges that have affected artists, with Copyright being the central point in the relationship between these parties. The objective of this article was to expand the analysis regarding the understanding of Copyright from the perspective of Comic Book authors. To this end, a descriptive study was conducted with a qualitative approach and content analysis methodology. The analysis revealed that this sector has limited knowledge about Copyright and is insecure about the unauthorized use of its works.